DNA methylome, transcriptome, and prostate cancer prevention by phenethyl isothiocyanate in TRAMP mice. Issue 6 (13th April 2021) - Wu, Renyi; Li, Shanyi; Sargsyan, Davit; Yin, Ran; Kuo, Hsiao‐Chen; Peter, Rebecca; Wang, Lujing; Hudlikar, Rasika; Liu, Xia; Kong, Ah‐Ng
Abstract: Epigenetics/epigenomics has been shown to be involved in carcinogenesis. However, how the epigenome would be altered in the transgenic adenocarcinoma of the mouse prostate (TRAMP) cancer model and the effect of cancer chemopreventive phytochemical phenethyl isothiocyanate (PEITC) on the epigenome in TRAMP mice are not known. PEITC has been reported to reduce the risk of many cancers including prostate cancer (PCa). In this study, male TRAMP mice were fed a control diet or diet containing 0.05% PEITC from 8 weeks to 16 weeks. The tumor incidence was reduced in the PEITC diet (0/6) as compared with the control diet (6/7). RNA‐sequencing (RNA‐seq) analyses on nontumor and tumor prostatic tissues revealed several pathways like cell cycle/Cdc42 signaling, inflammation, and cancer‐related signaling, were activated in prostate tissues of TRAMP mice but were reversed or attenuated in TRAMP mice fed with PEITC diet. DNA CpG methyl‐seq analyses showed that global methylation patterns of prostate samples from TRAMP mice were hugely different from those of wild‐type mice. Dietary PEITC partially reversed the global methylation changes during prostatic carcinogenesis. Integration of RNA‐seq and DNA methyl‐seq analyses identified a list of genes, including Adgrb1 and Ebf4, with an inverse regulatory relationship between their RNA expression and CpG methylation. In summary, our current study demonstrates that alteration of the global epigenome in TRAMP prostate tumor and PEITC administration suppresses PCa carcinogenesis, impacts global CpG epigenome and transcriptome, and attenuates carcinogenic pathways like cell cycle arrest and inflammation. These results may provide insights and epigenetic markers/targets for PCa prevention and treatment in human PCa patients.